Decomposição de polímero à base de enxofre para posterior determinação de Ca, Fe e Na por ICP OES - Fontanive, Fernando Cappelli (2010)
In this work different procedures were evaluated for the decomposition of a sulfur-based commercial polymer, with subsequent Ca, Fe and Na determination, elements present in additives, using inductively coupled plasma optical emission spectropscopy (ICP OES). The sample was decomposed using wet ashing with medium and high-pressure microwave ovens (30 and 80 bar, respectively), microwave-induced combustion (MIC) and dry ashing employing muffle type furnace, according to ASTM D 4004-06 method for elastomers decomposition. The decomposition using high pressure microwave oven was carried out using HNO3, while the medium pressure decomposition was performed with HNO3 and HNO3 + HF. The microwave-induced combustion was performed using 20 bar pressure with O2, 50 μL of 6 mol L-1 NH4NO3 as combustion aid and concentrated HNO3 as absorbing solution. The dry ashing decomposition according to the ASTM method consisted in furnace heating at 250 °C for 1 hour a nd 550 °C for 2 hours, with further residue dissolution using 6 mol L-1 HCl. Dry ashing was also performed using 250 °C for 1 hour and 600 °C for 2 hours heat ing, with residue dissolution using HF and HNO3 and heating with hot plate until nearly dry. After the procedures, all solutions exhibited solid residues, with exception of the wet ashing using HNO3 + HF, which showed no residue. No statistical difference was observed in analyte concentrations after wet ashing using HNO3 and HNO3 + HF, while the results obtained after MIC and dry ashing were lower than the other techniques. Wet ashing using HNO3 + HF was considered the most suitable when compared to the other procedures evaluated. Analyte concentration in this solution was 52424 ± 3556 μg g-1, 2986 ± 132 μg g-1 e 595 ± 56 μg g-1 for Ca, Fe e Na, respectively.